Metastatic melanoma in the small intestine: infrequent cause of perforation: case report - Romero, Lucía; Arcienega, Pilar; Telles, Leandro; González, Daniel (Cirugía del Uruguay, 2023)
Introduction: The small intestine is the most frequent site of metastatic melanoma. However, its diagnosis continues to be a challenge since it is usually asymptomatic or with non-specific symptoms.Few cases result in complications, peritonitis due to perforation being infrequent. The objective of the work is to report a clinical case of peritonitis due to perforation of a melanoma metastasis in the small intestine. Clinical case: A 66-year-old male patient diagnosed with melanoma of the neck and secondary bone, brain and lung melanoma, underwent emergency surgery for acute peritonitis due to perforation of metastasis in the small intestine, which was resected and anastomosed. The histology confirmed the secondary nature of the cutaneous melanoma. Conclusion: Knowing that the jejunum-ileum is the most frequent site of melanoma metastases, in the presence of non-specific digestive symptoms or anemia, its involvement should be suspected and possible therapeutic alternatives should be evaluated.